A Reception Analysis of Users of the Online Dating App Tinder as a Medium of Self Disclosure: Analisis Resepsi Pengguna Aplikasi Kencan Online Tinder Sebagai Media Self Disclosure - Dara Citra Nurani; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to shed light on user reception of the online dating application Tinder as a medium for self-disclosure, prompted by the surge in criminal activities and sexual violence incidents experienced by some users who readily engage with strangers in the virtual realm of social media dating. Employing qualitative research methods and Stuart Hall's encoding-decoding model, the study utilized in-depth interviews and purposive sampling for data collection. The qualitative analysis revealed three informants in a dominant position, two in opposition, and all informants engaged in negotiation. Key findings highlight user interest in Tinder's visually appealing features, including logos, colors, and messaging, along with a focus on the provided security measures and privacy policies. Notably, informants expressed reluctance to disclose personal information, deeming Tinder susceptible to criminal activities and sexual harassment. This study contributes valuable insights for enhancing the safety and user experience within online dating platforms. Highlights : User Perception: Explore how users perceive and engage with the Tinder app, focusing on visual elements and messaging features. Privacy Concerns: Uncover the hesitancy of users to disclose personal information due to perceived risks of criminal activities and sexual harassment. Security Measures: Highlight the importance of users' positive reception towards security features and privacy policies implemented by Tinder for ensuring a safer online dating experience. Keywords: Online Dating, Tinder, User Reception, Self-Disclosure, Safety